The relationship between effectiveness of job training and job satisfaction among academic staff at UiTM Pahang branch, Jengka Campus / Nur Izzati Abdullah - Abdullah, Nur Izzati (Faculty of Business and Management, 2019)
This project paper was conducted to fulfill the requirement needed by the Faculty of Business and Management, Universiti Teknologi MARA. The researcher had selected a topic entitled "The Relationship Betwen Effectiveness of Job Training and Job Satisfaction Among Academic Staff at UiTM Pahang Branch, Jengka Campus". This study was focused on the Kirkpatrick's model by Donal Kirkpatrick (1970) which is to measure of effectiveness of job training give as the independent variable and the Affect Theory from Locke (1976) for the job satisfaction as the dependent variable. This research focuses only on permanent staff and the overall respondents were 130. To identifiy the sampling size, the researcher used Krejcie and Morgan Table and the researcher used convenience random sampling technique to distribute the questionnaires. Job satisfaction had a significant effect on the reults based on the findings and results of analysis, the reseacher concluded that effectiveness job training from the perspective of the academic staff also know that the level of effectiveness of job training and job satisfaction are high among the academic staff.